Audit committee's effectiveness and financial reporting quality: the case of GLCs in Malaysia - Jamil, Nurul Nazlia; Puat Nelson, Sherliza (LAP Lambert Academic Publishing, 2012)

(untitled)
Financial reporting quality has been under scrutiny especially after the collapse of major companies. The main objective of this study is to investigate the audit committee’s effectiveness on the financial reporting quality among the Malaysian GLCs. In particular, the study examined the impact of audit committee characteristics (independence, size, frequency meeting and financial expertise) on earnings management in periods prior to and following the transformation program (2003-2009). As at 31 December 2010, there were 33 public-listed companies categorized as Government-Linked Companies (GLC Transformation Policy, 2010) and there were 20 firms that have complete data which resulted in the total number of firm-year observations to become 120 for six years (year 2003-2009). Results show that the magnitude of earnings management as proxy of financial reporting quality is influenced by the audit committee independence. However, no evidence was found to support the effect of audit committee size, meetings and expertise on the magnitude of earnings management. Agency theory and resource dependence theory were applied to explain audit committee, as a monitoring mechanism as well as reducing agency costs via gaining competitive advantage in knowledge, skills, and expertise towards financial reporting quality. However, contrary to expectation, the theories were not fully supported hence there is a need for other alternative theory that can explained the relationship in positive manner. This study is different from prior studies, in that it makes a significant contribution towards enhancing one’s knowledge in the interacting role of audit committee’s effectiveness and financial reporting quality subsequent to the transformation program in GLCs. The study is important as it provides additional knowledge about the impact of audit committee’s effectiveness on reducing the earnings management, and assist practitioners, policymakers and regulators such as Malaysian Institute of Accountants, Securities Commission and government to determine ways to enhance audit committee’s effectiveness and improve the financial reporting of GLCs, as well as improving the quality of the accounting profession.